At tænke teater, turde tage chancer og ikke stole på formler: – et blik på dramaturgiens aktuelle position og uddannelsens muligheder - Lehmann, Hans-Thies; Lohmann, Jesper (Peripeti, 2008)
The German professor of Theatre Studies argues for the necessity of educating dramaturgs with an open mind towards contemporary art and culture. Likewise he emphasizes the need for having the courage to experiment with new forms of expression and working methods.